Idiopathic facial aseptic granuloma of unusual size. - Nasi, L.; Alexopoulos, A.; Thanopoulou, I.; Dakoutrou, M.; Stefanaki, K.; Kakourou, T. (European Journal of Pediatric Dermatology, 2024)
Idiopathic facial aseptic granuloma (IFAG) is a rare granulomatous lesion typically occurring in early childhood. It is often considered part of the childhood rosacea spectrum. These lesions frequently occur together with concomitant eyelid chalazion, further strengthening their association with rosacea. Here we present the case of a 12-year-old girl diagnosed with large IFAG and successfully treated with oral clarithromycin and topical metronidazole ointment.